Ethics of Political Communication in Welcoming the Implementation of the 2024 General Election - Dedy Djamaluddin Malik (HK-Publishing, 2022)
The ethics of political communication has an essential function and determines the democratization system in Indonesia, besides that there is a battle of interests to influence, seize, maintain, and expand power carried out by political communicators, namely the elite (rulers) and the public. Meanwhile, in interpreting democratic involvement in the political system, it explains aspects from adherence to democratic norms and values to behaviors designed to affect the quality of life of the community at large. This research is a type of qualitative research, using a descriptive method, while the purpose of this study is to determine the extent of the role of political communication ethics in welcoming the 2024 general election in Indonesia. Politics as a process of controlling and coordinating all elements within the scope of government must always synergize with various interests of the wider community. In certain situations, political communication emphasizes the decision-making process rather than thinking about the impact of the decisions or policies made. This process is a mechanism to achieve a series of goals, especially in accommodating symbols of public interest and symbols of power. Political communication as a complex communication activity, involves many factors and components in it ranging from language, symbols, leading actors, media, society, and various public policies.